STRATEGI COPING DAN DUKUNGAN SOSIAL TERHADAP KELELAHAN EMOSIONAL PADA ORANG TUA ANAK BERKEBUTUHAN KHUSUS - Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2015)
The aim of this study is to analyze the influence of coping strategy and social support to the emotional exhaustion in the parents of the children with special needs. This is a cross sectional study which been carried out for 4 months in Hermina Hospital Bekasi. The population of this study are parents with children with special needs and being in therapy for more than 6 months, in Developomental Clinic Hermina Hospital Bekasi. The result of spearman test show that the correlation between coping strategy with emotional exhausted Besides, the result of spearman test between social support and emotional exhausted show that no correlation between social support and emotional exhausted.Based on the result of double regression analysis, coping strategy and social support have an influence to the emotional exhausted